The Effect of Corporate Governance, Audit Quality, and Auditor Turnover on The Integrity of Financial Statements: Empirical Study on Manufacturing Companies Listed on the Stock Exchange Indonesia Period 2016-2020 - Pangastuti, Eka Sylvia; Maini, Zumratul; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to prove and analyze the influence of Corporate Governance, Audit Quality, and Auditor Change on the Integrity of Financial Statements. The data source of this study uses secondary data obtained from manufacturing companies listed on the IDX. Sampling in this study used the purposive sampling method. The technical data analysis used in this study is a classical assumption test, multiple linear regression, and hypothesis test. The research data were processed using SPSS 26 to test the regression coefficient. Based on the results of partial research, it was found that independent commissioner variables and audit quality had a positive effect on the integrity of financial statements, while auditor turnover variables had a negative effect on the integrity of financial statements and managerial ownership variables did not affect the integrity of financial statements